Mastering JavaScript design patterns write reliable code to create powerful applications by mastering advanced JavaScript design patterns - Timms, Simon (Packt Publishing, 2016)
Annotation
Online resource; title from PDF title page (EBSCO, viewed August 30, 2016)
Keywords: JavaScript (Computer program language); Software patterns; Computer software -- Reusability; Scripting languages (Computer science); JavaScript (Langage de programmation); Logiciels; Modèles de conception; Logiciels; Réutilisation; Langages de script (Informatique); COMPUTERS; Programming Languages; JavaScript; Computer software; Reusability